The Importance Of Smart Manufacturing Technology In Bernas Factory: Bernas Sungai Limau, Kedah - MOHAMAD MAHAYUDIN, NUR AWANIS (Journal of Islamic, Social, Economics and Development, 2025)
Purpose - This study looks at the importance of smart manufacturing technology at the BERNAS Sungai Limau factory to meet the full needs of Malaysians in terms of demand rice which is 2.69 million tons per year. Methodology - This study was conducted on 10 BERNAS Sungai Limau factory employees using a qualitative method where data collection and data interpretation are done in depth before being analyzed to the conclusion of the study. Findings - With the existence of artificial intelligence, Iot and cloud computing in smart manufacturing it can open new opportunities for innovation to various sectors. The results of the study found that there are four importance of smart manufacturing to BERNAS factory in Sungai Limau, Kedah namely time effective, increase productivity, maintaining the sustainability and increase rural development. Research limitations - This study was conducted at the BERNAS Sungai Limau factory only, where it involved a very limited study sample. This causes a lack of diversity in research findings. Practical implication - Policy implications in the context of the three policies involved, namely the National Agro-Food Policy 2021-2030, the Rural Development Policy 2021-2020 and the Science, Technology and Industry Policy 2021-2020.